Derivatives in reading behind bin Hisham al-Bazzar Morphological study (Journal of the College of Education for Women, 2019)
One of the main criteria taken by the reader in the correct reading of a statement is the standard morphological, Vabv Eetmisah from the rest of science that examines the word andchanges therein lead to new meanings, which is the rule months in Morphology, every increase in construction lead to an increase in meaning.Who took behind with the likes of ten readers Morphology a way to show the most rightly reading, to perform the desired effect, it has committed as committed behind bin Hisham statement argument morphological under which the clear sense of the formula of distinguished from Matheladtha of formulas feature to perform their intended meaning. And here that God Almighty was meant to each formula is contained in verse without the other; what each incoming feature version differs from the others.Was the order of topics morphological Aloradh in the search, according to the direction taken by the reader behind the bin Hisham al-Bazzar, then the statement is approved by the readers and with whom disagreed.And show morphological arguments adopted in the correct reading, which represents the face, which is taken by it and the readers of vision statement that, with a statement of morphological Alhhj which bucked that argument.We have adopted in've listed the arguments on revenues scientists said in their books, especially the meanings of the Qur'an and expressing, and wrote commentaries, books morphological and grammatical.Notably, we did not find the behind bin Hisham Bazaar, one of the ten readers, and read it correct, and shear in prayer as classified wrote readings, read by himself in it or argument calculated to him, the approach agreed with the previous readers adopted, and this is what we found through the study derivatives in reading behind bin Hisham Bazaar.